Pengaruh Lingkungan Kerja Terhadap Semangat Kerja Pegawai Pada Kantor Camat Ambalawi Bima: The Influence of the Work Environment on Employee Morale at the Ambalawi District Head's Office, Bima - Sahrul, Alfi; Yusuf, Muhammad; Amirulmukminin, Amirulmukminin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Efforts to achieve organizational goals can be made by maintaining employee morale. High morale, characterized by enthusiasm in carrying out tasks, is influenced by various factors, including the work environment. This study aims to determine the influence of the work environment on the morale of employees at the Ambalawi District Head's Office, Bima. The research method used is associative research with a quantitative approach. The object of the research is the work environment as the independent variable and work morale as the dependent variable, with the research subjects being the employees at the Ambalawi District Head's Office, Bima. The research population consisted of 70 people, and a sample of 54 respondents was selected using purposive sampling. Data were collected through observation, Likert scale questionnaires, and literature review. The data analysis technique used was simple linear regression with the help of the SPSS program. The results showed that the work environment has a significant influence on the morale of employees at the Ambalawi District Head's Office, Bima. The coefficient of determination indicates that the work environment affects morale by 69.5%, while the remainder is influenced by other variables not examined in this study.